2012
DOI: 10.1080/19371918.2010.494991
|View full text |Cite
|
Sign up to set email alerts
|

Do Empowerment Strategies Facilitate Knowledge and Behavioral Change? The Impact of Family Health Advocacy on Health Outcomes

Abstract: This study evaluates the impact of a Family Health Advocacy (FHA) intervention on 46 African American women ages 13 to 35 living in a rural southern community. FHA utilizes empowerment strategies to provide education and social support to reduce risk factors for poor pregnancy outcomes. Use of a paired t test demonstrated a statistically significant difference between pretest and posttest scores in the acquisition of knowledge of safer sex practices, alcohol consumption, early prenatal care, maternal infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…physical activity, screen-related behaviour of children), one of which being healthy nutrition. Except for the study by Baffour and Chonody (28) , the quantitative studies revealed significant improvements in nutrition-related (parenting) behaviour to varying extents due to the intervention. Both Backman et al (20) and Jurkowski et al (31) assessed empowerment as an outcome in their studies.…”
Section: Study Characteristicsmentioning
confidence: 81%
See 4 more Smart Citations
“…physical activity, screen-related behaviour of children), one of which being healthy nutrition. Except for the study by Baffour and Chonody (28) , the quantitative studies revealed significant improvements in nutrition-related (parenting) behaviour to varying extents due to the intervention. Both Backman et al (20) and Jurkowski et al (31) assessed empowerment as an outcome in their studies.…”
Section: Study Characteristicsmentioning
confidence: 81%
“…1). Table 1 provides an overview of the main characteristics of the eight included studies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) . All studies were performed in Anglophone or Scandinavian countries within the last two decades.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations